Improving the Economy of Quebec: A Study of Retail E-commerce Sales Factors - Trudel, Mildred (Université d'Ottawa / University of Ottawa, 2023)
The internet has enabled billions of online transactions with customers transacting in real-time from various geographical points, while ecommerce could make more for Quebec traders dealing in various commodities. Quebec's ecommerce is still underdeveloped. This thesis seeks to understand the factors behind an e-consumer making a purchasing decision on a Quebec ecommerce site by using the Online Purchase assessment tool (OPAT) model to pinpoint emerging e-commerce trends, a literature review, and a questionnaire to discover the reality of why consumers purchase online. It discovered that e-commerce is not well-developed in Quebec because platforms use French and leave out English-speaking shoppers, most residents prefer physical shopping, and poor pricing strategies by foreign ecommerce platforms. This study aims to uncover why the Quebec retail industry is underdeveloped when it has enormous potential to lead among Canadian provinces. It evaluates consumer purchasing behaviors from online stores based on three moments that happen during the purchasing process. Summarily, it measures the first moment a retailer visits the platform, when they decide to purchase, and loyalty when they return to purchase again. It also provides recommendations for Quebec retailers regarding factors to consider when setting up their ecommerce stores to be successful.
Keywords: Autonomy; client's satisfaction; convenience; e-confidence; consumer; e-loyalty; enjoyment; trust; market position; reputation; purchase; responsiveness; moments